2016
DOI: 10.1016/j.alit.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil chemotaxis assay in nasal polyps by using a novel optical device EZ-TAXIScan: Role of CC-chemokine receptor 3

Abstract: The CCR3 pathway may play an important role in the pathogenesis of eosinophil recruitment in nasal polyps through selective eosinophil chemotaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The presence of mucosal eosinophilia is correlated with disease severity and clinically distinct subsets of CRS [1517]. The pathophysiology of tissue eosinophilia is incompletely known, but Th2 cytokines including IL-5 and eotaxins play an indispensable role in eosinophil-selective accumulation, similar to other allergic diseases [12, 18]. Of note, approximately 30 % of tissue eosinophils in CRSwNP exhibit ultrastructural evidence of cytolysis [19].…”
Section: Lessons From Chronic Rhinosinusitis: Pathogenesis Of Eosinopmentioning
confidence: 99%
“…The presence of mucosal eosinophilia is correlated with disease severity and clinically distinct subsets of CRS [1517]. The pathophysiology of tissue eosinophilia is incompletely known, but Th2 cytokines including IL-5 and eotaxins play an indispensable role in eosinophil-selective accumulation, similar to other allergic diseases [12, 18]. Of note, approximately 30 % of tissue eosinophils in CRSwNP exhibit ultrastructural evidence of cytolysis [19].…”
Section: Lessons From Chronic Rhinosinusitis: Pathogenesis Of Eosinopmentioning
confidence: 99%
“…In our study, we found that the control or surrounding colonic tissue of the distal colon harbors 13-20 eosinophils/HPF, whereas the polyp tissue showed a significantly higher frequency of cells (43,06+/-22,32 eosinophils/HPF), along with significantly increased levels of CCL26 in the epithelial compartment. Other authors have reported similar results in nasal polyps, with a high tissue content of chemokines and high eosinophil count (13). Furthermore, CCL26 has also been described as produced by human bronchial epithelial cells (14) and keratinocytes (15) and its imbalanced secretion, probably due to an overexpression of type-2 cytokines, was implicated in atopic dermatitis and asthma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 63%
“…Previous literature has reported several factors implicated in eosinophil development, homing, and survival, including Eotaxin 19,20 , IL-5 [21][22][23][24] , and others 7,8,25 . To determine which factors may be influencing eosinophil development and survival in the IL7R mutant mice, we collected serum from WT and mutant mice and compared the relative concentration of several cytokines.…”
Section: Il7r Deletion Caused Alterations In Cytokines Involved In Mymentioning
confidence: 99%
“…We found that two known eosinophil regulators, Eotaxin and IL-5, were reduced in the IL7Rα -/mice. Both of these cytokines are known to be secreted by lymphoid cells to promote eosinophil development, homing, and survival 19,20,[22][23][24]29 . Additionally, as previously reported 7 , we observed that IL-7 was upregulated in the IL7R -/mice, likely due to unbound excess IL-7 in the absence of lymphoid cells.…”
Section: Il7r Deletion Caused Alterations In Cytokines Involved In Mymentioning
confidence: 99%